Association of Accuracy, Conclusions, and Reporting Completeness With Acceptance by Radiology Conferences and Journals. Issue 2 (8th January 2022) - Frank, Robert A.; Fabiano, Nicholas; Hallgrimson, Zachary; Korevaar, Daniël A.; Cohen, Jérémie F.; Bossuyt, Patrick M.; Leeflang, Mariska M. G.; Moher, David; McInnes, Matthew D. F.; ,; Treanor, Lee; Salameh, Jean‐Paul; et al.
Abstract : Background: Preferential publication of studies with positive findings can lead to overestimation of diagnostic test accuracy (i.e. publication bias). Understanding the contribution of the editorial process to publication bias could inform interventions to optimize the evidence guiding clinical decisions. Purpose/Hypothesis: To evaluate whether accuracy estimates, abstract conclusion positivity, and completeness of abstract reporting are associated with acceptance to radiology conferences and journals. Study Type: Meta‐research. Population: Abstracts submitted to radiology conferences (European Society of Gastrointestinal and Abdominal Radiology (ESGAR) and International Society for Magnetic Resonance in Medicine (ISMRM)) from 2008 to 2018 and manuscripts submitted to radiology journals ( Radiology, Journal of Magnetic Resonance Imaging [JMRI]) from 2017 to 2018. Primary clinical studies evaluating sensitivity and specificity of a diagnostic imaging test in humans with available editorial decisions were included. Assessment: Primary variables (Youden's index [YI > 0.8 vs. <0.8], abstract conclusion positivity [positive vs. neutral/negative], number of reported items on the Standards for Reporting of Diagnostic Accuracy Studies [STARD] for Abstract guideline) and confounding variables (prospective vs. retrospective/unreported, sample size, study duration, interobserver agreement assessment, subspecialty, modality) were extracted. Statistical Tests: Multivariable logistic regression to obtain adjusted odds ratio (OR) as a measure of the association between the primary variables and acceptance by radiology conferences and journals; 95% confidence intervals (CIs) and P ‐values were obtained; the threshold for statistical significance was P  < 0.05. Results: A total of 1000 conference abstracts (500 ESGAR and 500 ISMRM) and 1000 journal manuscripts (505 Radiology and 495 JMRI ) were included. Conference abstract acceptance was not significantly associated with YI (adjusted OR = 0.97 for YI > 0.8; CI = 0.70–1.35), conclusion positivity (OR = 1.21 for positive conclusions; CI = 0.75–1.90) or STARD for Abstracts adherence (OR = 0.96 per unit increase in reported items; CI = 0.82–1.18). Manuscripts with positive abstract conclusions were less likely to be accepted by radiology journals (OR = 0.45; CI = 0.24–0.86), while YI (OR = 0.85; CI = 0.56–1.29) and STARD for Abstracts adherence (OR = 1.06; CI = 0.87–1.30) showed no significant association. Positive conclusions were present in 86.7% of submitted conference abstracts and 90.2% of journal manuscripts. Data Conclusion: Diagnostic test accuracy studies with positive findings were not preferentially accepted by the evaluated radiology conferences or journals. Evidence Level: 3 Technical Efficacy: Stage 2.